Storm drains and level ditches - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
On sloping land, storm ditches can protect land from erosion, while level ditches increase infiltration of rainwater runoff.